Standardization Harmonization, Consolidation, and Refinement of Draft Laws in DPR and DPD - Chandra, M Jeffri Arlinandes; Wahanisa, Rofi; Kosasih, Ade; Barid, Vera Bararah (The Indonesian Journal of International Clinical Legal Education, 2023)
The Purpose of this research is to find a formula for harmonizing, consolidating, and refining the concept of draft laws. Harmonization activities are based on policy formulation (regulation system) and material harmonization (substance), with the aim of adjusting the existing national legal system to the new legal system, creating a harmonious law as a positive law (harmony of law). The plural nature of the places where harmonization, consolidation, and refinement of the concept of draft laws occur are the Indonesian House of Representatives (DPR) - Committee on Legislation (Baleg), the Government - Ministry of Law and Human Rights (Depkumham), and the Regional Representative Council (DPD) - Committee on Legislation and PPUU. This makes the practice of harmonization have different interpretations from each institution, which highlights the need for agreement among these institutions in determining standardization in harmonization, consolidation, and refinement of the concept of draft laws. Furthermore, an analysis is needed to determine the appropriate time for harmonization, consolidation, and refinement of the concept of draft laws, whether it should be done before submitting the bill as is currently done, or after discussions are completed, or both before and after. Therefore, it is necessary to investigate the effectiveness of the implementation of the activities of harmonizing, consolidating, and refining the concept of draft laws to minimize the filing of judicial reviews at the Constitutional Court.